The danger of being overly attached to the concrete: the case of division by zero - Lajoie, Caroline; Mura, Roberta (NOMAD Nordic Studies in Mathematics Education, 1998)
In this article, we use the example of division by zero to illustrate how reliance on concrete representations of mathematical concepts can become an obstacle to understanding. We describe some difficulties encountered by prospective elementary teachers in dealing with division by zero and we show how these difficulties could be explained by the students’ desire for a (non-existent) physical interpretation of the mathematical problem.